첨두강우강도를 고려한 우수관로 및 빗물펌프장의 설계용량 검토 - 정건희; 심규범; 김응석; Chung, Gunhui; Sim, Kyu Bum; Kim, Eung Seok (Journal of Korea Water Resources Association, 2014)
Stormwater pipe systems are most commonly used to discharge rainwater from the urban catchment covered by the impervious area. To design stormwater pipe and rainwater pumping station, frequency analysis is implemented using historical rainfall and the design rainfall is timely distributed using theoretical shape such as Huff distribution. This method cannot consider the rainfall intensity variation caused by climate change which is type of uncertainty. Therefore, in this study, runoff from Gasan1 stormwater pumping stations catchment is calculated using design rainfall distributed by the 2nd quartile distribution method and the historical rainfall events. From the analysis, the nodal flooding in the urban catchment is likely caused by the high peak rainfall event rather than the large amount of rainfall. The linear regression analysis is implemented. As a result, when several storms have the same amount of rainfall, the nodal flooding in the stormwater pipe systems could be caused by the high peak of storm events. Since as the storm duration become short, the peak rainfall become high, the nodal flooding likely become severe with the short storm duration. The uncertainty in the peak data of design rainfall is analyzed and this uncertainty has to be consider in the stormwater pipe design process. 불투수지역이 대부분인 도시유역의 경우, 우수관을 통한 우수의 배제가 유출시스템의 대부분을 차지한다. 도시지역의 우수관로 및 빗물펌프장의 용량을 설계하기 위해서는 일반적으로 강우빈도해석을 통해 계산된 빈도별 강우를 Huff시간분포 등을 사용하여 일괄적으로 시간 분포시켜 유출을 계산한다. 그러나 이러한 설계는 기후변화 등으로 인해 게릴라성 호우 등이 빈번히 발생하고, 평균적인 강우강도가 증가하고 있는 현실의 불확실성을 제대로 반영하지 못한다. 그러므로 본 연구에서는 설계강우사상의 첨두강우강도가 가지는 불확실성을 분석하기 위해, 설계강우사상을 시간 분포시키는 대표적인 방법이며, 실제 본 연구의 적용지역인 가산1빗물펌프장의 설계에 사용된 Huff 2분위 방법과 과거 발생한 실제 강우사상들을 이용한 유출해석을 실시하였다. 그 결과, 유역 내 지체효과가 거의 없는 도시지역의 경우에는 총강우량보다는 첨두강우강도에 의해 유역 내 홍수가 유발된다는 것을 확인하였고, 이를 입증하기 위해 회귀분석을 수행하였다. 즉, 총강우량이 같다고 하더라도, 첨두강우강도에 따라 상류 우수관의 범람이 야기될 수 있으며, 이러한 현상은 같은 빈도의 설계강우량이라고 해도 지속시간이 짧은 경우에 더 큰 첨두강우강도를 가지므로 더욱 두드러졌다. 이것을 본 연구에서는 설계강우사상를 시간분포시킴에 의해 야기되는 첨두강우강도의 불확실성이라고 정의하고, 이에 대한 정량화 및 고려가 도시지역의 유출시스템 설계 시 고려되어야 함을 제안하였다.